Preference for Cyber-Counselling among Students of Federal University of Kashere, Gombe State - Alfayo , Samuel Boh (Kashere Journal of Education, 2025)
This study was carried out to investigate the preference for cybercoaching among Students at the Federal University of Kashere, Gombe State, with reference to Lagos State University. The study specifically looks at how easy it is for students at the Federal University of Kashere, Gombe State, to access cyber-counselling services, whether they prefer cyber-counselling, how effective it is for them, and what problems are stopping them from using these services. The study employed the survey descriptive research design. A total of 259 responses were validated from the survey. From the responses obtained and analysed, the findings revealed that there is a preference for cyber-counselling among Students of the Federal University of Kashere, Gombe State. The study thereby recommends that University counselling centres should organise numerous workshops and sensitisation programmes on the effortless utilisation of online counselling to sustain and improve the positive attitude university students have towards online counselling. Additionally, the study recommends that teachers and academic advisors use more online counselling techniques to address their students' needs when they approach them. Finally, seminars and symposia will be held on the importance of online counselling to generate interest in such services.